Tripyridinium cis-tetrachloridodioxidomolybdate(VI) chloride - Fernandes, José A. (2018)
In the title compound, (C(5)H(6)N)(3)[MoCl(4)O(2)]Cl, the pyridinium cations are N-H center dot center dot center dot Cl hydrogen bonded to the anionic [MoCl(4)O(2)](2-) complexes and to the two crystallographically independent chloride anions (located on C2 axes). The Mo(6+) centre adopts a highly distorted octahedral geometry, being surrounded by four chloride and two terminal oxide groups. The oxide ligands are mutually cis.